The Development of Mathematics Learning Media Course Modules integrated with Riau Malay Culture on Mathematics Education Students of State Islamic University Sultan Syarif Kasim Riau - Noviarni, Noviarni; Hasibuan, Ismail Mulia; Nurdin, Erdawati; Amelia, Rizki (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2023)
The outcomes of creating a media program for mathematics education students at UIN Suska Riau that incorporates Riau Malay culture are presented in this article. This study employed the Plomp paradigm of developmental research, utilizing questionnaires, interview summaries, and module performance analysis. The data analysis results indicated that the mathematics learning media module based on Riau Malay culture was classified as very valid with an average validity of 87.15%; the practicality level percentage in the small group trial was 75% (practical); following revision, the practicality level percentage in the limited group trial was 88.8% (very practical). Based on the results of the module performance that the ability of students who use the module is better than the ability of students who do not use the module, it means that the Riau Malay culture-based mathematics learning media module is declared effective with t count = 5.13 greater than t table = 1.73 where the average experimental class (85.26) is higher than the control class (78.79). This is supported by the results of interviews that show students who use the module are directed and helped greatly in preparing integrated mathematics learning media of Riau Malay culture. These results are based on the performance results of the module, which show that the ability of students who use the module is better than the ability of students who do not use it.